2017
DOI: 10.1016/j.jsv.2017.08.038
|View full text |Cite
|
Sign up to set email alerts
|

An implementation of an aeroacoustic prediction model for broadband noise from a vertical axis wind turbine using a CFD informed methodology

Abstract: This paper presents an enhanced method for predicting aerodynamically generated broadband noise produced by a Vertical Axis Wind Turbine (VAWT). The method improves on existing work for VAWT noise prediction and incorporates recently developed airfoil noise prediction models. Inflow-turbulence and airfoil self-noise mechanisms are both considered. Airfoil noise predictions are dependent on aerodynamic input data and time dependent Computational Fluid Dynamics (CFD) calculations are carried out to solve for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 38 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…However, it is still important to conduct noise prediction during the early stage turbine design so that its integration into urban environments can be approved. Botha et al [45] developed on optimised technique for calculating aerodynamically produced noise by a small VAWT. This technique enhances the current prediction of noise and integrates currently established aerofoil prediction models.…”
Section: Micro-small Scalementioning
confidence: 99%
“…However, it is still important to conduct noise prediction during the early stage turbine design so that its integration into urban environments can be approved. Botha et al [45] developed on optimised technique for calculating aerodynamically produced noise by a small VAWT. This technique enhances the current prediction of noise and integrates currently established aerofoil prediction models.…”
Section: Micro-small Scalementioning
confidence: 99%
“…It was shown that this method could reduce the noise level up to 56%. Botha et al 20 proposed an aeroacoustic prediction model for VAWT application which was based on the CFD approach. The purpose was to find out the mechanism and location of aerodynamic noise emitted from VAWT rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding noise, VAWTs usually have a tip speed, which is half the tip speed of horizontal axis wind turbines, and therefore are more silent [2] and can be better suited for urban turbines. Unsteady Reynolds Averages Navier-Stokes simulations have also been used to propose silent VAWTs [31], to study silent airfoils for VAWTs [32] and to derive broadband noise models [33]. In this work we retain a Large Eddy Simulation approach.…”
Section: Introductionmentioning
confidence: 99%